Resistance, but not endurance exercise training, induces changes in cerebrovascular function in healthy young subjects - Thomas, Hannah J.; Marsh, Channa E.; Naylor, Louise H.; Ainslie, Philip N.; Smith, Kurt J.; Carter, Howard H.; Green, Daniel J. (American journal of physiology. Heart and circulatory physiology, 2021)
Three months of endurance exercise did not elicit adaptation in any domain of cerebrovascular function in young healthy inactive volunteers. However, resistance training induced decreased pulsatility in the extracranial arteries and increased cerebrovascular resistance in cerebral arteries. This increase in cerebrovascular resistance, apparent at baseline and in response to both hypercapnia and acute exercise, may reflect a protective response in the face of changes in arterial pressure during resistance exercise. It is generally considered that regular exercise maintains brain health and reduces the risk of cerebrovascular diseases such as stroke and dementia. Since the benefits of different “types” of exercise are unclear, we sought to compare the impacts of endurance and resistance training on cerebrovascular function. In a randomized and crossover design, 68 young healthy adults were recruited to participate in 3 mo of resistance and endurance training. Cerebral hemodynamics through the internal carotid, vertebral, middle and posterior cerebral arteries were measured using Duplex ultrasound and transcranial Doppler at rest and during acute exercise, dynamic autoregulation, and cerebrovascular reactivity (to hypercapnia). Following resistance, but not endurance training, middle cerebral artery velocity and pulsatility index significantly decreased ( P < 0.01 and P = 0.02, respectively), whereas mean arterial pressure and indices of cerebrovascular resistance in the middle, posterior, and internal carotid arteries all increased ( P < 0.05). Cerebrovascular resistance indices in response to acute exercise and hypercapnia also significantly increased following resistance ( P = 0.02), but not endurance training. Our findings, which were consistent across multiple domains of cerebrovascular function, suggest that episodic increases in arterial pressure associated with resistance training may increase cerebrovascular resistance. The implications of long-term resistance training on brain health require future study, especially in populations with pre-existing cerebral hypoperfusion and/or hypotension. NEW & NOTEWORTHY Three months of endurance exercise did not elicit adaptation in any domain of cerebrovascular function in young healthy inactive volunteers. However, resistance training induced decreased pulsatility in the extracranial arteries and increased indices of cerebrovascular resistance in cerebral arteries. This increase in cerebrovascular resistance, apparent at baseline and in response to both hypercapnia and acute exercise, may reflect a protective response in the face of changes in arterial pressure during resistance exercise. Listen to this article’s corresponding podcast at https://ajpheart.podbean.com/e/exercise-and-cerebrovascular-function/ .